Head Trauma in the Eurasian Lynx (Lynx lynx dinniki) - Arican, Mustafa; Hilmican Ergin; Yasemin Tanirli; Süleyman Serhat İyigün; Elgin Orçum Uzunlu (Acta Scientiae Veterinariae, 2025)
Background: The Eurasian Lynx lynx dinniki is in danger of extinction in Iran and Turkey. Many wild animals are injured in traffic accidents every year. Head trauma is a common cause of morbidity and mortality in small animals. To ensure the best outcome in such patients, a rapid diagnosis should be made and early treatment should be started. In this case report, we describe the current emergency trauma procedure for a lynx with head trauma. In addition, the biochemical and clinical examination parameters noted during the examination are given for the 1st time as a contribution to the literature. Case: A 2-4-month-old female Lynx lynx dinniki, weighing 1.7 kg, was brought to Emergency Clinic of the Veterinary Faculty, Selcuk University, by the Forestry officials of the Ministry of Agriculture, with complaint of traffic accident. On examination, the lynx was found to be making unconscious flapping movements with its forelimbs and was unresponsive to the environment. Detailed examination with a fundus camera of both eyes revealed foci of arterial and venous haemorrhages in the fundus layer. Radiographic examination showed no abnormal findings in the thorax. However, oedema in the skull and effusion in the abdomen were observed. The effusion was transudate. During the treatment phase, daily transamine [10 mg/kg, IM], vitamin K [1 mL/kg, SC], prednisolone [0.5 mg/kg], mannitol [1 mg/kg], isotonic solution [1 mL/min to 100 mL, IV] in an animal intensive care unit with 56% humidity, 240C temperature and continuous oxygen, isotonic solution [1 mL/min to 100 mL IV], dextrose [1 mL/min to 3 mL IV], duphalayte [1 mL/min to 5 mL IV], vitamin C [50 mg/kg, SC], vitamin B12 [40 mcg/kg] and ceftriaxone [40 mg/kg, IV] for prophylaxis. Normal ambulation on day 11 of treatment. Discussion: The causes of death in lynxes have been identified in 5 main categories: disease, fighting, road accidents, poaching and unknown causes. Disease-related mortality was determined on the basis of molecular analyses, macroscopic findings, microbiology and histopathology. Traffic accidents and trauma are among the leading causes. Therefore, 1st aid is needed depending on the severity of trauma and lesions. In this case report, Trauma triage and modified Glasgow coma scale scores, which were used for the 1st time in a Lynx lynx dinniki, were thought to provide a lower mortality rate by allowing objective measurement of trauma-specific disease severity and injury severity. For the case presented here, although some values are available in the literature for lynxes, some values were tried to be discussed by adapting them to cats. WBC value was found to be high in the lynx. In the case presented, granulocytosis and monocytosis were considered to develop due to traumatic injury. In the present case, the cause of thrombocytopenia is thought to be the development of consumptive coagulopathy due to head trauma. In this case, upper limit Na and high Cl values were found in blood gases. High blood Na and Cl values are thought to be dehydration developing after trauma. Blood CPK and glucose values were found to be high. Low serum albumin and total protein amount are thought to cause abdominal effusion with transudate character. Hypoalbuminemia, hypoproteinaemia, low BUN and creatine levels are thought to be related to malnutrition developing after trauma. In this case, the reason for hyperbilirubinemia in the patient is thought to be increased bilirubin production due to tissue damage caused by trauma. Keywords: animal trauma triage score, modified Glasgow coma scale, lynx.